PROBLEMS AND CLOUD COMPUTING BASED SOLUTIONS WITH THE SUGGESTED DATABASE FOR ARCHAEOLOGICAL VISITORS - Robinson, A.Jerome; Satyanarayana, K.; Muthukumaravel, A. (International Journal of Psychosocial Rehabilitation, 2020)
Cloud Computing is going to modify the approaches of users who using the resources in the internet. In this research Article, the problems facing by the visitors and the Cloud based solutions as a data model can be provided with its usage. If the visitor accompany with this model, this will help the visitor in various aspects such as planning in travel, boarding place, destination of journey, Hotels, Restaurants, mode of travel to reach the monument, route map according to the budget specified by the user, the area statistics and pollution factor with necessary prevention equipments with the feedbacks, ratings and reviews of the previous visitors. These implementations also can be applicable to other fields.